2019
DOI: 10.1253/circj.cj-18-1002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Assessment Chart by Dietary Factors in Japan ― NIPPON DATA80 ―

Abstract: benefits of consuming several food groups for the reduction of CVD risk. 11-15 However, it is also important for the clinical setting and preventive medicine to show the recommended amount of each food. Japanese people are well known to have a high salt intake, and salt consumption is known to be an independent risk factor for CVD. 9 Therefore, salt intake is an important consideration if associations between diet and CVD risk are to be established for Japanese people. In the present study, we constructed a ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 48 publications
0
27
1
Order By: Relevance
“…After screening the title and abstract, forty-five studies were selected for full-text evaluation. By full-text examination, twenty-five articles were eventually included for data synthesis with 2,027,512 participants and 103,734 CVD deaths [ 11 , 13 , 14 , 15 , 16 , 17 , 18 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After screening the title and abstract, forty-five studies were selected for full-text evaluation. By full-text examination, twenty-five articles were eventually included for data synthesis with 2,027,512 participants and 103,734 CVD deaths [ 11 , 13 , 14 , 15 , 16 , 17 , 18 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies, involving 1,267,951 participants and 51,628 CVD deaths, investigated the association between the fish intake and the CVD mortality risk [ 13 , 14 , 15 , 16 , 17 , 18 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 40 ]. The pooled RR (95% CI) was 0.91 (0.85–0.98) for the highest versus the lowest fish consumption category (I 2 = 70.0%) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 43 articles were eligible for a full-text review. Among the 43 articles reviewed, 36 [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] met all the inclusion criteria ( Figure 1 ). Twenty-four studies were included for highest versus lowest meta-analysis between dietary sodium intake and CVD risk.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies were included for highest versus lowest meta-analysis between dietary sodium intake and CVD risk. For the dose-response meta-analysis, we excluded 4 studies [ 35 , 49 , 62 , 68 ] because they only compared the highest and lowest sodium intake categories. After estimating the trends in the dose-response meta-analysis, eight studies reported coefficients between dietary sodium intake and CVD risk, which were added to the studies in the dose-response meta-analysis.…”
Section: Resultsmentioning
confidence: 99%